2011
DOI: 10.1016/j.jvs.2011.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic function predicts survival after renal revascularization

Abstract: Purpose To define the relationship between left ventricular diastolic function and survival after renal revascularization. Methods 76 adult patients (49 women, 27 men; mean age: 63 years ± 13 years) with preoperative echocardiography who underwent renal revascularization for atherosclerotic disease were identified. Diastolic function was estimated from the early diastolic transmitral flow velocity (E), the atrial transmitral flow velocity (A) and the mitral annular tissue doppler velocity (e’). Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Improved coronary circulation could contribute to the balance between myocardial energy requirements and oxygen supply, and relief of myocardial stiffness. A previous cohort study had demonstrated that diastolic function was significantly and independently associated with BP response and follow-up survival in patients undergoing open renal revascularization (Ghanami et al, 2011). The extent of systolic BP improvement in our study was more significant in the HFpEF-I group than in the HFpEF-II group.…”
Section: Discussionsupporting
confidence: 45%
“…Improved coronary circulation could contribute to the balance between myocardial energy requirements and oxygen supply, and relief of myocardial stiffness. A previous cohort study had demonstrated that diastolic function was significantly and independently associated with BP response and follow-up survival in patients undergoing open renal revascularization (Ghanami et al, 2011). The extent of systolic BP improvement in our study was more significant in the HFpEF-I group than in the HFpEF-II group.…”
Section: Discussionsupporting
confidence: 45%